Reduced DTI-ALPS in H-type hypertension: insights into perivascular space function - Chun Zhang; Chun Zhang; Caihong Song; Shiying Sheng; Liang Pan; Lingling Sun; Wei Xing (Frontiers in Neurology)
Recent studies suggest that glymphatic dysfunction plays a significant role in vascular cognitive impairment (VCI). Both hypertension and hyperhomocysteinemia are independent risk factors for VCI, and their combination is referred to as H-type hypertension (HHT). However, the impact of HHT on glymphatic function remains unclear. This study used the recently popular indirect marker, diffusion tensor imaging along the perivascular space (DTI-ALPS) to assess potential changes in glymphatic function in patients with HHT. We recruited 58 HHT patients and 50 healthy controls without hypertension, collecting clinical, cognitive, biochemical, and diffusion MRI data. Behaviorally, HHT patients scored lower on global cognitive tests compared to controls. DTI-ALPS analysis revealed a bilateral reduction in DTI-ALPS in HHT patients. Correlation analysis showed strong associations between lower DTI-ALPS values, reduced cognitive scores, and elevated homocysteine (Hcy) levels in HHT patients. Mediation analysis further indicated that DTI-ALPS largely mediates the relationship between Hcy levels and cognitive performance. These findings suggest that hypertension and elevated Hcy levels contribute to DTI-ALPS reduction, which may underlie the cognitive decline observed in HHT.